A Study on the Packaging Information of Antibiotics Available in Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
The samples of primary and secondary packaging items of antibiotics manufactured in Bangladesh or imported by local distributing agencies, were collected and thoroughly examined from 2009 to 2010 on the basis of 32 parameters. These parameters are usually regarded important for the labeling of any drug, from the view point of standards set by national regulatory agencies, such as Directorate General of Drug Administration (DGDA) and Bangladesh Standards and Testing Institution (BSTI). The primary and secondary packaging items of a total of 10 pharmaceutical industries have been collected, sorted/arranged and meticulously studied, and packaging parameters were accumulated for analysis. It has been observed that many of the important packaging information were either completely missing or not properly described on the labels, inserts, inner carton, outer carton and container. This study was aimed at examining to what extent the packaging information is provided in the primary and secondary packaging items of antibiotics. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22300 Bangladesh Pharmaceutical Journal 16(2): 171-176, 2013